Scholastic Florence : Moral Psychology in the Quattrocento. - Edelheit, Amos (Brill's studies in intellectual history., 2014)
The focuse in this book is on different concepts and theories pertaining to moral psychology, showing the complex relations between scholastic and humanist thinkers who stand between antiquity and modernity, in the Renaissance setting.